A dança Sussa no município de Cavalcante/Goiás: possibilidades no contexto educacional - Ferraz, Thais Gomes (2022)
This dissertation presents the results of an investigation about the sussa dance, developed during the Professional Master's in Teaching in Basic Education of the Stricto Sensu Postgraduate Program of CEPAE/UFG, between the years 2019 to 2022, whose educational product presented is the digital book: “Let's dance sussa?” This qualitative and ethnographic research presents as a design a study regarding the Sussa dance in the Kalunga Vão de Almas Community and in the city of Cavalcante. The theme to be investigated is the research and presentation of the Sussa dance, so that it can become a possibility of content to be introduced at school in different areas of knowledge. It was proposed, therefore, as specific objectives: To know the history of the women dancers of Sussa in the municipality of Cavalcante and the community of Vão de Almas; to present information on the development and characteristics of Sussa, coming from the region where the women dancers of Sussa reside; develop a product that can be used to introduce Sussa into the school environment. The methodology was developed in phases that focus on: bibliographic survey, observations, field diary, interviews, capture of videos and photographs and analysis and interpretation of the data collected. Four women living in the city of Cavalcante and in the community of Vão de Almas were interviewed, who were nominated for showing recognition among residents of the city of Cavalcante in their life stories and for presenting relationships with the Sussa dance. For data analysis, we used Bardin's content analysis. Among the results found, through the methodology used, it was possible to obtain relevant information for the construction of knowledge originating in Sussa and in the life stories of women, which contribute to the strengthening of their culture, also bringing, in their speeches, the interest of the manifestation of the Sussa dance in the school space. We conclude, therefore, that the Sussa dance as a content in Basic Education can favor the discussion about the Afro-Brazilian culture and the decolonization of dance.